Digital Piracy as a Socio-Cultural Practice: A study of the Greek Market - Arouh, Melania; Miliopoulou, Georgia-Zozeta (Kinephanos)

(untitled) (Université de Montréal Département d'histoire de l'art et d'études cinématographiques, 2024)
The illegal file sharing of digital content is a widespread activity with far-reaching ramifications. In Greece, studies indicate that “digital piracy” has become an accepted form of criminal practice, disrupting relevant market developments. To explore this, we conducted an online questionnaire that documented practices of Greek audiences, regarding the piracy of movies and television series. This paper goes beyond the labelling of the practice to an analysis of its socio-cultural character. We argue that these findings point to a changing market, and the disruption piracy causes is explained as an effort by consumers to participate in a global culture that transcends national borders.